Pemanfaatan Limbah Cair Industri Tahu Harapan Maju, Cimanggis, Depok sebagai Media Kultur Spirulina sp. - Mustamina Maulani; Asri Nugrahanti; Mohammad Apriniyadi; Bayu Satyawira; Zakiah Darajat Nurfajrin; Gabriella Jasmine; Henry David Young; Rakha Handika Putra (Abdimas Universal, 2022)
Industrial waste in Depok still a problem raised because its contents were not following the government’s quality standards. Contaminants were considered pollutant are Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), and Total Suspended Solids (TSS) were quite high. One of these wastes was tofu wastewater which produced a foul odor and pollutes the environment when discharged directly into water bodies. Lack of industrial owners' education of the economic value of the waste caused direct disposal without being utilized first. Therefore, this Community Service activity aims to determine the feasibility of tofu industrial wastewater as a Spirulina sp. culture medium and provided education to the tofu factory owners, to utilize their liquid waste. In the implementation several stages are carried out, namely literature studies, sampling, implementing wastewater assessments, counseling also training. The result of this activity is tofu industrial wastewater can be utilized as a medium for cultivating Spirulina sp. which added economic value while reducing the environmental pollution. This can be seen from the results of Spirulina cultivation on the 10th day where the Optical Density (OD) continues to increase and harvested for further use.